Coptidis Rhizoma Suppresses Metastatic Behavior by Inhibiting TGF-β-Mediated Epithelial-Mesenchymal Transition in 5-FU-Resistant HCT116 Cells - Kang, Yong-Hwi; Wang, Jing-Hua; Lee, Jin-Seok; Lee, Nam-Hun; Son, Chang-Gue (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is the second most lethal malignancy worldwide. The high mortality rate of CRC is largely due to cancer metastasis. Recently, suppressing epithelial-to-mesenchymal transition (EMT) has been considered a promising strategy for treating metastatic cancer, especially drug-resistant metastatic cancer. The present study aimed to evaluate the antimetastatic effect of Coptidis Rhizoma, as well as the potential underlying mechanisms, using a 5-fluorouracil-resistant colon tumor cell model (HCT116/R). Coptidis Rhizoma 30% ethanol extract (CRE) significantly inhibited HCT116/R cells migration and invasion. CRE effectively inhibited EMT in HCT116/R cells by upregulating the expression of an epithelial marker (E-cadherin) and downregulating the expression of mesenchymal markers (vimentin, Snail, and ZEB2) at both the protein and gene levels. Immunofluorescence assays also confirmed consistent patterns in the levels of E-cadherin and vimentin. In addition, the anti-EMT activity of CRE and its related effects were associated with the CRE-mediated suppression of the TGF-β pathway, as shown by changes in the levels of downstream molecules (phosphorylated Akt and p38), and inhibition of migration and invasion after treatment/cotreatment with a TGF-β inhibitor (SB431542). In conclusion, Coptidis Rhizoma exerts a potential antimetastatic effect, especially in the treatment of drug-resistant cancer, and the possible mechanisms are associated with inhibiting EMT via TGF-β signaling. Thus, Coptidis Rhizoma will likely become a potential therapeutic candidate for simultaneously mitigating drug resistance and metastasis in CRC.